Feasibility of Healthy and Fresh Smoothies: Opportunities and Challenges from the Consumer Perspective in Central Cikarang - Sari, Nadilah Sintia; Permana, Muhammad Rizki; Mauizhoh, Nida Wahdah; Sagita, Lisna; Muslihat, Rivaldi (Lentera Ilmu Nusantara, 2025)
This study examines the opportunities and challenges of the